Correlation Between Cigarette Smoking and Blood Pressure (BP) In Baghdad City. (Texas Journal of Agriculture and Biological Sciences, 2023)
Tobacco uses and high blood pressure are two main contributors to cardiovascular disease, Iraq's leading cause of death. In Iraq, the correlation among smoking with blood pressure (BP) is unknown. This study looked at the variations in (SBP) systolic BP as well as (DBP) diastolic BP between daily average cigarette smokers and nonsmokers in Baghdad adults aged 19 to 82 years using information collected from various hospitals in Baghdad city from December to April 2023 patients and the Healthy Survey. A total of 300 persons, 280 patients included 160 men and 120 women with 20 health control divided into 10 men and 10 women their data matches the patients. With their valid blood pressure measurement, age, gender, socio economic, blood viscosity in multivariate regression linear regression analysis, these serve as potential confounders. The study group was divided into two aged group (19-44) years and (45-82) years. Analyses were provided to detect a variation in systolic blood pressure among smokers 2.2 mm Hg higher than nonsmokers in males. Whereas Female smokers had considerably lower SBP and DBP (mean difference 2 mm) than non-smokers. Older smokers for both genders have higher diastolic BP. There were no such differences between younger patients either for DBP in same age group. Lower blood pressure in female tobacco users in Baghdad city may be described by the effects of daily cigarette smoking in women, or by unmeasured confounding factors related with a traditional way of life that may lower blood pressure (For instance, diet and exercise).